Increase in root branching enhanced ferric-chelate reductase activity under iron stress in potato (Solanum tuberosum) - CHALLAM, CLARISSA; DUTT, SOM; SUDHAKAR, DURAIALAGARAJA; RAVEENDRAN, MUTHURAJAN; BUCKSETH, TANUJA; SINGH, RAJESH KUMAR (The Indian Journal of Agricultural Sciences, 2021)
In response to Fe-deficiency, various dicots increase their root branching to improve ferric-chelate reductase activity. It still remains unclear, whether the response caused by Fe-deficiency ultimately improves the plant’s ability to withstand Fe-deficiency. In this experiment conducted at ICAR-Central Potato Research Institute, Regional Station, Shillong during 2020, we demonstrated a substantial increase in the growth of the lateral root of potato genotype (CP 3443), when grown in the iron-stress, in relation to control plants, and the total lateral root number is well linked to ferric-chelate reductase (FCR) activity. These findings showed that FCR is involved in root Fe uptake in potato (Solanum tuberosum L.) and they suggest a role in Fe distribution throughout the plant. In view of these findings, the Fe-deficiency induced increases in the lateral roots suggested that these play a significant role in Fe-deficiency tolerance in potato, which can serve as useful trait for the identification of chlorosis tolerance and/or nutrient-deficiency stress.